A visible-to-middle infrared biomimetic camouflage device based on multi-field synergistic regulation and a preparation method and application thereof
Patent Information
- Application Number
- CN202610987189.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-03
- Publication Date
- 2026-10-13
AI Technical Summary
[0005]基于上述现有技术的不足,本发明的目的在于提供一种基于多场协同调控的可见-中红外仿生伪装器件及其制备方法与应用,旨在解决现有伪装技术中可见光与红外波段调控耦合强、缺乏独立动态调控能力的问题
[0016]有益效果:本发明通过仿生“功能解耦、多场协同”策略,实现了可见光与中红外波段的独立调控。具体地,通过磁场或压力调控电解质层中超顺磁纳米颗粒晶格间距可独立改变可见光颜色(调制可见光),通过电压调控电致发射率调制层材料的离子/电子/载流子浓度来改变材料对红外光的吸收和反射,进而可独立改变中红外发射率(调制发射率),二者互不干扰,解决了传统技术中波段调控耦合强的核心难题。同时,本发明提供的器件可响应磁场、压力和电场等多种外部刺激,环境适应性强。本发明提供的器件在可见光波段可实现全色域连续可调,在中红外3~5 μm与8~14 μm大气窗口发射率调制率分别达0.314和0.249,表观温度变化为8.9℃,响应时间低于2秒,满足动态伪装需求。此外,通过调控磁场空间分布可实现器件的可编程图案化显示,为复杂背景下的自适应伪装提供了灵活高效的解决方案。
Smart Images

Figure CN122902142A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomimetic camouflage device technology, and in particular to a visible-mid-infrared biomimetic camouflage device based on multi-field synergistic modulation, its preparation method and application. Background Technology
[0002] Currently, researchers have developed various spectral camouflage techniques. Visible light camouflage primarily achieves color modulation by constructing photonic crystal structures or dynamic surface wrinkles (Proceedings of the National Academy of Sciences, 2021, 118: e2114345118); infrared camouflage mainly relies on the Stefan-Boltzmann law, reducing the target surface temperature through heat-insulating layers or using low-emissivity coatings to modulate the infrared emissivity of the material surface (ACS Nano, 2023, 17: 6875). However, most existing technologies suffer from strong coupling to band modulation, insufficient dynamic modulation capabilities, and a single response mode. As modern reconnaissance technologies develop towards multi-band, full-spectrum coverage, the aforementioned functional camouflage techniques, primarily targeting single visible or infrared bands, are increasingly unable to meet the demands of complex environments due to their inherent "spectral mismatch" defects.
[0003] Therefore, developing a biomimetic camouflage device that can achieve independent, dynamic, and programmable control of visible and mid-infrared bands and respond to a variety of external stimuli is a technical challenge that urgently needs to be solved in this field.
[0004] Therefore, existing technologies still need to be improved and developed. Summary of the Invention
[0005] Based on the shortcomings of the existing technology, the purpose of this invention is to provide a visible-mid-infrared biomimetic camouflage device based on multi-field synergistic modulation, its preparation method and application, aiming to solve the problems of strong coupling between visible light and infrared band modulation and lack of independent dynamic modulation capability in existing camouflage technologies.
[0006] The technical solution of the present invention is as follows: In a first aspect, the present invention provides a visible-mid-infrared biomimetic camouflage device, wherein the visible-mid-infrared biomimetic camouflage device comprises a transparent window layer, an electroemissivity modulation layer, an electrolyte layer and a counter electrode layer stacked sequentially. The electrolyte layer includes an electrolyte matrix and superparamagnetic nanoparticles dispersed in the electrolyte matrix; The electroemission modulation layer includes at least one of aluminum-doped zinc oxide nanoparticles, carbon nanotubes, graphene, tungsten oxide, lithium titanate, and nickel oxide.
[0007] Optionally, the visible-mid-infrared biomimetic camouflage device further includes a transparent conductive layer located between the electroemissivity modulation layer and the electrolyte layer.
[0008] Optionally, the transparent window layer comprises one of BaF2, ZnS, ZnSe, polycarbonate, and polymethyl methacrylate; And / or, The superparamagnetic nanoparticles are superparamagnetic Fe3O4 nanoparticles, and polyvinylpyrrolidone is bonded to the surface of the superparamagnetic Fe3O4 nanoparticles.
[0009] Optionally, the surface of the superparamagnetic Fe3O4 nanoparticles is bonded with polyvinylpyrrolidone via tannic acid.
[0010] Optionally, the superparamagnetic Fe3O4 nanoparticles with polyvinylpyrrolidone bonded to their surface via tannic acid have a particle size of 50–300 nm.
[0011] Optionally, the electrolyte matrix includes a liquid electrolyte matrix or a gel electrolyte matrix; The liquid electrolyte matrix comprises a first lithium salt and a first organic solvent; The gel electrolyte matrix is formed by curing a second lithium salt, polymer monomer, crosslinking agent and photoinitiator.
[0012] A second aspect of the present invention provides a method for preparing the visible-mid-infrared biomimetic camouflage device as described above, comprising the following steps: Provide a transparent window layer; An electroemissivity modulation layer, an electrolyte layer, and a counter electrode layer are sequentially formed on the surface of the transparent window layer to obtain the visible-mid-infrared biomimetic camouflage device.
[0013] Optionally, an aluminum-doped zinc oxide nanoparticle dispersion is applied to the surface of the transparent window layer, and after annealing, an electroemissivity modulation layer is formed. The preparation method of the aluminum-doped zinc oxide nanoparticle dispersion includes the following steps: Zinc acetate dihydrate, aluminum acetylacetonate, and oleic acid were mixed, heated and stirred under vacuum, and then oleylamine was injected and the mixture was heated and stirred again. The resulting mixture was then injected into oleyl alcohol preheated to 220-300°C for reaction. After centrifugation and purification, aluminum-doped zinc oxide nanoparticles were obtained. The aluminum-doped zinc oxide nanoparticles were dispersed in a second organic solvent to obtain an aluminum-doped zinc oxide nanoparticle dispersion.
[0014] Optionally, the electrolyte layer contains superparamagnetic Fe3O4 nanoparticles with polyvinylpyrrolidone bonded to their surface via tannic acid. The preparation method of the superparamagnetic Fe3O4 nanoparticles with polyvinylpyrrolidone bonded to their surface via tannic acid includes the following steps: Tannic acid and polyvinylpyrrolidone were added to a third organic solvent and reacted at a temperature of 130-180°C. The mixture was then cooled to a preset temperature, ferric chloride hexahydrate was added, and stirring was continued. After cooling to room temperature, sodium acetate was added, and the mixture was stirred and reacted at a temperature of 180-220°C for 4-20 hours to obtain superparamagnetic Fe3O4 nanoparticles with polyvinylpyrrolidone bonded to their surface by tannic acid.
[0015] A third aspect of the present invention provides an application of the visible-mid-infrared biomimetic camouflage device described above in the fields of military camouflage, intelligent thermal control, or dynamic display.
[0016] Beneficial Effects: This invention achieves independent control of the visible and mid-infrared bands through a biomimetic "functional decoupling and multi-field synergy" strategy. Specifically, the visible light color can be independently changed (modulated visible light) by adjusting the lattice spacing of superparamagnetic nanoparticles in the electrolyte layer using a magnetic field or pressure. The absorption and reflection of infrared light by the material in the electroemissivity modulation layer can be altered by adjusting the ion / electron / carrier concentration using voltage, thereby independently changing the mid-infrared emissivity (modulated emissivity). These two methods do not interfere with each other, solving the core problem of strong coupling in band control in traditional technologies. Simultaneously, the device provided by this invention can respond to various external stimuli such as magnetic fields, pressure, and electric fields, exhibiting strong environmental adaptability. The device provides full-color-gamut continuous tunability in the visible light band, with emissivity modulation rates of 0.314 and 0.249 in the mid-infrared 3-5 μm and 8-14 μm atmospheric windows, respectively. The apparent temperature change is 8.9℃, and the response time is less than 2 seconds, meeting the requirements of dynamic camouflage. Furthermore, programmable patterned displays can be achieved by controlling the spatial distribution of the magnetic field, providing a flexible and efficient solution for adaptive camouflage in complex backgrounds. Attached Figure Description
[0017] Figure 1 This is a schematic diagram of a visible-mid-infrared biomimetic camouflage device.
[0018] Figure 2 This is a schematic diagram illustrating the synthesis principle of Fe3O4@TA@PVP nanoparticles.
[0019] Figure 3 This is a schematic diagram of the visible-mid-infrared biomimetic camouflage device in Example 1.
[0020] Figure 4Scanning electron microscope (SEM) images and particle size distribution statistics of Fe3O4@TA@PVP nanoparticles prepared at different temperatures (135℃, 130℃, and 160℃, respectively) in Examples 1, 2, and 3.
[0021] Figure 5 The image shows a transmission electron microscope (TEM) image and elemental distribution diagram of the Fe3O4@TA@PVP nanoparticles prepared at 135℃ in Example 1.
[0022] Figure 6 The hysteresis loop diagrams are for Fe3O4@TA@PVP nanoparticles prepared at different temperatures (135℃, 130℃ and 160℃, respectively) in Examples 1, 2 and 3.
[0023] Figure 7 The images shown are transmission electron microscope (TEM) images and LSPR curves of the AZO nanoparticles prepared in Example 1. (a) is a TEM image at low magnification, (b) is a TEM image at high magnification, and (c) is an LSPR curve.
[0024] Figure 8 The images show the reflectance and visible light modulation results of the visible-mid-infrared biomimetic camouflage devices prepared in Examples 1, 2, and 3 under different magnetic field strengths. Specifically, (a) shows the reflectance of the device prepared in Example 2 under different magnetic field strengths, (b) shows the reflectance of the device prepared in Example 1 under different magnetic field strengths, (c) shows the reflectance of the device prepared in Example 3 under different magnetic field strengths, (d) shows the visible light modulation results of the device prepared in Example 2 under different magnetic field strengths, (e) shows the visible light modulation results of the device prepared in Example 1 under different magnetic field strengths, and (f) shows the visible light modulation results of the device prepared in Example 3 under different magnetic field strengths.
[0025] Figure 9 The graph shows the mid-infrared emissivity curves of the visible-mid-infrared biomimetic camouflage device in Example 1 under different voltages.
[0026] Figure 10 The images shown are infrared imaging results and apparent temperature variation curves of the visible-mid-infrared bionic camouflage device under different applied voltages in Example 1. (a) is the infrared imaging result image, and (b) is the apparent temperature variation curve.
[0027] Figure 11 The images shown are mid-infrared emissivity results and infrared imaging results of the visible-mid-infrared biomimetic camouflage device in Example 1 under different magnetic field strengths, where (a) is the mid-infrared emissivity result image and (b) is the infrared imaging result image.
[0028] Figure 12 The images show the reflection spectrum of the visible-mid-infrared bionic camouflage device in Example 1 under different voltages and the actual device image, where (a) is the reflection spectrum of the visible light band and (b) is the actual device image.
[0029] Figure 13 The image shows the modulation spectrum of the visible-mid-infrared biomimetic camouflage device in Example 1 under magnetic and electric fields in multiple visible-mid-infrared bands.
[0030] Figure 14 The image shows the visible camouflage effect of the visible-mid-infrared bionic camouflage device in Example 1 against different colored backgrounds.
[0031] Figure 15 This is a photograph of the gel electrolyte used in Example 4, where the finger is pressed to apply pressure. Detailed Implementation
[0032] This invention provides a visible-mid-infrared biomimetic camouflage device based on multi-field synergistic modulation, its fabrication method, and its application. To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the invention is further described in detail below. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention.
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.
[0034] The terms used in this document, such as “vertical,” “horizontal,” “up,” “down,” “left,” “right,” and similar expressions, are for illustrative purposes only and do not represent the only possible implementation.
[0035] In this invention, unless otherwise explicitly specified and limited, "above" or "below" the second feature can mean that the first feature is in direct contact with the second feature, or that the first feature is in indirect contact with the second feature through an intermediate medium. Furthermore, "above," "over," and "on top" of the second feature can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.
[0036] If the embodiments of the present invention involve descriptions such as "first" or "second", such descriptions are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated.
[0037] This invention provides a visible-mid-infrared biomimetic camouflage device, such as... Figure 1 As shown, the visible-mid-infrared biomimetic camouflage device includes a transparent window layer 1, an electroemissivity modulation layer 2, an electrolyte layer 4, and a counter electrode layer 5, which are stacked sequentially. The electrolyte layer includes an electrolyte matrix and superparamagnetic nanoparticles dispersed in the electrolyte matrix; The electroemission modulation layer includes at least one of aluminum-doped zinc oxide nanoparticles, carbon nanotubes, graphene, tungsten oxide, lithium titanate, and nickel oxide.
[0038] This invention achieves independent modulation of the visible and mid-infrared bands through a biomimetic strategy of "functional decoupling and multi-field synergy." Specifically, the visible light color can be independently changed by adjusting the lattice spacing of superparamagnetic nanoparticles in the electrolyte layer through magnetic field or pressure, and the absorption and reflection of infrared light by the material can be changed by adjusting the ion / electron / carrier concentration of the electroemissivity modulation layer material through voltage, thereby independently changing the mid-infrared emissivity. These two methods do not interfere with each other, solving the core problem of strong coupling in band modulation in traditional technologies. Simultaneously, the device provided by this invention can respond to various external stimuli such as magnetic fields, pressure, and electric fields, exhibiting strong environmental adaptability. The device provided by this invention achieves continuous tunability across the entire color gamut in the visible light band, and achieves emissivity modulation rates of 0.314 and 0.249 in the mid-infrared 3–5 μm and 8–14 μm atmospheric windows, respectively, with an apparent temperature change of 8.9°C and a response time of less than 2 seconds, meeting the requirements of dynamic camouflage. Furthermore, programmable patterned displays of the device can be achieved by adjusting the spatial distribution of the magnetic field, providing a flexible and efficient solution for adaptive camouflage in complex backgrounds.
[0039] For example, when the material of the electroemissivity modulation layer is aluminum-doped zinc oxide nanoparticles, the number of electrons injected into the aluminum-doped zinc oxide nanoparticles can be continuously controlled by applying a voltage, thereby controlling the free carrier concentration in the aluminum-doped zinc oxide nanoparticles and changing the local surface plasmon resonance absorption intensity, thus achieving modulation of the mid-infrared emissivity.
[0040] The electrolyte layer contains superparamagnetic nanoparticles. Under the influence of an external magnetic field, these nanoparticles align according to the magnetic field distribution, and their lattice spacing can change with variations in magnetic field strength. Based on Bragg's diffraction law, they selectively reflect visible light wavelengths, thus exhibiting different structural colors. Alternatively, the superparamagnetic nanoparticles can be pre-arranged in an ordered manner under a magnetic field, and then pressure can be applied to change the lattice spacing and alter the color.
[0041] In some implementations, such as Figure 1 As shown, the visible-mid-infrared biomimetic camouflage device further includes a transparent conductive layer 3, which is located between the electroemissivity modulation layer 2 and the electrolyte layer 4. The counter electrode layer 5 and the transparent conductive layer 3 together form an electric field loop.
[0042] In some embodiments, the transparent conductive layer comprises a transparent conductive metal oxide, which includes at least one of indium tin oxide, aluminum-doped zinc oxide, and fluorine-doped tin oxide, but is not limited thereto.
[0043] In some embodiments, the transparent window layer comprises one of BaF2, ZnS, ZnSe, polycarbonate, and polymethyl methacrylate. In this embodiment, the transparent window layer using the above materials has high transmittance in the visible and infrared bands. Specifically, BaF2 has a transmittance >90% in the visible light (380~780 nm) band and a transmittance >95% in the mid-infrared (3~5 μm and 8~14 μm) bands, providing a low-loss window for the incident and emitted light of multiple wavelengths.
[0044] In some embodiments, the superparamagnetic nanoparticles are superparamagnetic Fe3O4 nanoparticles, and the surface of the superparamagnetic Fe3O4 nanoparticles is coated with polyvinylpyrrolidone (PVP). In this embodiment, the superparamagnetic Fe3O4 nanoparticles with PPVP coated on the surface exhibit good and stable dispersibility and excellent magnetic responsiveness. As a surfactant, PPVP can increase the steric hindrance between the superparamagnetic Fe3O4 nanoparticles, ensuring the structural integrity and long-term dispersion stability of the superparamagnetic Fe3O4 nanoparticles.
[0045] In some implementations, such as Figure 2 As shown, the surface of the superparamagnetic Fe3O4 nanoparticles is bonded with polyvinylpyrrolidone via tannic acid.
[0046] In this embodiment, the superparamagnetic Fe3O4 nanoparticles with polyvinylpyrrolidone bonded to their surface by tannic acid can be referred to as superparamagnetic composite nanoparticles (denoted as Fe3O4@TA@PVP nanoparticles). The Fe3O4@TA@PVP nanoparticles include superparamagnetic Fe3O4 nanoparticles and polyvinylpyrrolidone (PVP) bonded to the surface of the superparamagnetic Fe3O4 nanoparticles by tannic acid (TA).
[0047] Specifically, such as Figure 2 As shown, the abundant phenolic hydroxyl groups in the tannic acid (TA) molecule react with Fe... 3+ Strong coordination bonds can be formed between the tannins, while the hydroxyl and carbonyl groups in the tannin molecules can form a strong hydrogen bond network with the polyvinylpyrrolidone (PVP) segments, thus firmly grafting the PVP shell onto the surface of the superparamagnetic Fe3O4 nanoparticles. This interface design based on the synergistic effect of coordination and hydrogen bonding effectively enhances the bonding strength of the PVP shell, ensuring the integrity of the overall structure and long-term dispersion stability, and maintaining its superparamagnetic properties.
[0048] In some embodiments, the superparamagnetic composite nanoparticles (denoted as Fe3O4@TA@PVP nanoparticles) have a particle size of 50~300 nm, specifically 100~200 nm.
[0049] In some embodiments, the electrolyte matrix includes a liquid electrolyte matrix or a gel electrolyte matrix.
[0050] In some embodiments, the liquid electrolyte matrix includes a first lithium salt and a first organic solvent.
[0051] In some embodiments, the gel electrolyte matrix is formed by curing a second lithium salt, a polymer monomer, a crosslinking agent, and a photoinitiator.
[0052] The first lithium salt and the second lithium salt each independently include at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalateborate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, and lithium hexafluoroarsenate, but are not limited thereto.
[0053] The first organic solvent includes, but is not limited to, at least one of N-methylacetamide, propylene carbonate, ethylene glycol dimethyl ether, dimethyl sulfoxide, and tetraethylene glycol dimethyl ether. The polymer monomer may be 4-acryloylmorpholine, the crosslinking agent may be polyethylene glycol diacrylate, and the photoinitiator may be 1-hydroxycyclohexylphenyl ketone.
[0054] When the electrolyte layer includes a liquid electrolyte matrix and superparamagnetic nanoparticles dispersed in the liquid electrolyte matrix, under the action of an external magnetic field, the superparamagnetic nanoparticles are arranged according to the magnetic field distribution, and the lattice spacing of the superparamagnetic nanoparticles can be changed according to the change of magnetic field strength. Based on the Bragg diffraction law, selective reflection of visible light wavelengths is achieved, thereby presenting different structural colors.
[0055] When the electrolyte layer includes a gel electrolyte matrix and superparamagnetic nanoparticles dispersed in the gel electrolyte matrix, the polymer monomer, crosslinking agent and photoinitiator are mixed with the superparamagnetic nanoparticles. The superparamagnetic nanoparticles can be pre-gelled under the action of a magnetic field to make them arrange in an orderly manner. Then, the color of the superparamagnetic nanoparticles is changed by applying pressure to change the lattice spacing of the superparamagnetic nanoparticles.
[0056] In some embodiments, the thickness of the transparent window layer is 0.5 to 3 mm, for example, it can be 0.5 mm, 1 mm, 1.5 mm, 2 mm, 2.5 mm or 3 mm.
[0057] In some embodiments, the thickness of the electroemissivity modulation layer is 0.2~2 μm, for example, it can be 0.2 μm, 0.5 μm, 0.8 μm, 1 μm, 1.2 μm, 1.5 μm, 1.8 μm or 2 μm.
[0058] In some embodiments, the thickness of the electrolyte layer is 0.1 to 2 mm, for example, it can be 0.1 mm, 0.2 mm, 0.5 mm, 0.8 mm, 1 mm, 1.2 mm, 1.5 mm, 1.8 mm or 2 mm.
[0059] In some embodiments, the thickness of the counter electrode layer is 0.02~1 μm, for example, it can be 0.02 μm, 0.05 μm, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm or 1 μm, etc.
[0060] In some embodiments, the thickness of the transparent conductive layer is 100~500 nm, for example, it can be 100 nm, 200 nm, 300 nm, 400 nm or 500 nm.
[0061] This invention also provides a method for preparing the visible-mid-infrared biomimetic camouflage device as described above, comprising the following steps: S11, Provides a transparent window layer; S12. An electroemissivity modulation layer, an electrolyte layer, and a counter electrode layer are sequentially formed on the surface of the transparent window layer to obtain the visible-mid-infrared biomimetic camouflage device.
[0062] This invention also provides another method for preparing the visible-mid-infrared biomimetic camouflage device described above, comprising the following steps: S21. Provide a transparent window layer; S22. An electroemissivity modulation layer, a transparent conductive layer, an electrolyte layer, and a counter electrode layer are sequentially formed on the surface of the transparent window layer to obtain the visible-mid-infrared biomimetic camouflage device.
[0063] The device fabricated using the method provided in this invention enables independent control of the visible and mid-infrared bands. Specifically, the visible light color can be independently altered by controlling the lattice spacing of superparamagnetic nanoparticles in the electrolyte layer using a magnetic field or pressure. The absorption and reflection of infrared light by the material in the electroemissivity modulation layer can be changed by controlling the ion / electron / carrier concentration using voltage, thereby independently altering the mid-infrared emissivity. These two methods do not interfere with each other, solving the core problem of strong coupling in band control in traditional technologies. Simultaneously, the device provided by this invention can respond to various external stimuli such as magnetic fields, pressure, and electric fields, exhibiting strong environmental adaptability. The device provides continuous tunability across the entire color gamut in the visible light band, with emissivity modulation rates of 0.314 and 0.249 in the mid-infrared 3–5 μm and 8–14 μm atmospheric windows, respectively. The apparent temperature change is 8.9 °C, and the response time is less than 2 seconds, meeting the requirements for dynamic camouflage. Furthermore, programmable patterned displays can be achieved by controlling the spatial distribution of the magnetic field, providing a flexible and efficient solution for adaptive camouflage in complex backgrounds.
[0064] In steps S11 and S21, the thickness and material of the transparent window layer are as described above and will not be repeated here.
[0065] In steps S12 and S22, the thickness and materials of the electroemissivity modulation layer, electrolyte layer, counter electrode layer, and transparent conductive layer are as described above and will not be repeated here.
[0066] In some embodiments, an aluminum-doped zinc oxide nanoparticle dispersion is applied to the surface of the transparent window layer, and after annealing, an electroemissivity modulation layer is formed. The preparation method of the aluminum-doped zinc oxide nanoparticle dispersion includes the following steps: Zinc acetate dihydrate, aluminum acetylacetonate, and oleic acid were mixed, heated and stirred under vacuum, and then oleylamine was injected and stirred again. The resulting mixture was then injected into oleyl alcohol preheated to 220-300°C for reaction. After centrifugation and purification, aluminum-doped zinc oxide nanoparticles were obtained. The aluminum-doped zinc oxide nanoparticles are dispersed in a second organic solvent (such as n-hexane) to obtain an aluminum-doped zinc oxide nanoparticle dispersion.
[0067] In some embodiments, the electrolyte layer contains superparamagnetic Fe3O4 nanoparticles (i.e., superparamagnetic composite nanoparticles) with polyvinylpyrrolidone bonded to their surface via tannic acid. The preparation method of the superparamagnetic composite nanoparticles includes the following steps: Tannic acid and polyvinylpyrrolidone are added to a third organic solvent (such as ethylene glycol) and reacted at a temperature of 130~180℃. The temperature is then lowered to a preset temperature (such as 65℃), ferric chloride hexahydrate is added, and stirring is continued. After cooling to room temperature, sodium acetate is added, and the mixture is stirred and reacted at a temperature of 180~220℃ for 4~20 hours to obtain superparamagnetic Fe3O4 nanoparticles with polyvinylpyrrolidone bonded to the surface by tannic acid.
[0068] In some embodiments, the transparent conductive layer can be prepared by magnetron sputtering or vapor deposition.
[0069] In some embodiments, when the electrolyte layer comprises a liquid electrolyte matrix and superparamagnetic nanoparticles dispersed in the liquid electrolyte matrix, the liquid electrolyte matrix is a mixed solution of lithium bis(trifluoromethanesulfonylimide) and N-methylacetamide.
[0070] When the electrolyte layer comprises a gel electrolyte matrix and superparamagnetic nanoparticles dispersed in the gel electrolyte matrix, the preparation method of the electrolyte layer includes the following steps: Lithium bis(trifluoromethanesulfonylimide), polymer monomers, crosslinking agents, photoinitiators, and superparamagnetic nanoparticles were mixed and cured to obtain an electrolyte layer.
[0071] The preparation method of the electrolyte layer specifically includes the following steps: lithium bis(trifluoromethanesulfonylimide), propylene carbonate, 4-acryloylmorpholine, polyethylene glycol diacrylate, 1-hydroxycyclohexylphenyl ketone and superparamagnetic nanoparticles are mixed and cured under ultraviolet light to obtain the electrolyte layer.
[0072] This invention also provides an application of the visible-mid-infrared bionic camouflage device described above in the fields of military camouflage, intelligent thermal control, or dynamic display.
[0073] The present invention will be further described below through specific embodiments.
[0074] In the following embodiments, unless otherwise specified, the raw materials and equipment used are all commercially available products.
[0075] In the following embodiments, some symbols have the following meanings: TA: Tannic acid; PVP: Polyvinylpyrrolidone; AZO: Aluminum-doped zinc oxide.
[0076] Example 1 This embodiment provides a method for fabricating a visible-mid-infrared biomimetic camouflage device based on multi-field synergistic modulation, including the following steps: (1) Synthesis of Fe3O4@TA@PVP nanoparticles (i.e., superparamagnetic composite nanoparticles): 0.36 g of TA was added to 90 mL of ethylene glycol and stirred at room temperature for 5 minutes. The mixture was then transferred to an oil bath preheated to 135 °C. After the temperature stabilized, 15.0 g of PVP was slowly added and stirred at 135 °C for 20 minutes to obtain a uniform and transparent solution. After the system cooled naturally to 65 °C, 1.62 g of ferric chloride hexahydrate (FeCl3·6H2O) was added and stirred at 65 °C for 40 minutes to obtain a dark green solution. The dark green solution was removed and slowly cooled to room temperature. Then, 8.4 g of sodium acetate (NaAc) was slowly added and stirred vigorously for 30 minutes. The resulting mixture was transferred to a polytetrafluoroethylene-lined reactor and reacted at 200 °C for 12 hours. After the reaction, the product was separated using a neodymium iron boron magnet and washed three times with ethanol. Finally, the product was dispersed in 80 mL of ethanol for later use to obtain a Fe3O4@TA@PVP nanoparticle dispersion.
[0077] (2) Synthesis of AZO nanoparticles based on continuous growth method: 1.0432 g (4.75 mmol) zinc acetate dihydrate, 0.0156 g (0.048 mmol) aluminum acetylacetonate, and 4.8 mL oleic acid were mixed and magnetically stirred at 110 °C under vacuum for 20 minutes. Then, 4.8 mL oleylamine was injected into the system, and stirring was continued at 100 °C under vacuum for 5 minutes to obtain a pretreated precursor solution. The system was then switched to a nitrogen atmosphere and maintained at this temperature for later use. 16 mL of oleyl alcohol was taken and vacuumed at 120 °C to remove water and oxygen. Then, the temperature was raised to 280 °C under nitrogen protection. 2.4 mL of the pretreated precursor solution was slowly injected into oleyl alcohol at 280 °C and reacted for 1 hour. After the reaction was completed, the mixture was cooled, purified by centrifugation, and dispersed in 15 mL of n-hexane to obtain an AZO nanoparticle dispersion.
[0078] (3) Preparation of magnetically responsive liquid electrolyte: 3.85 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 5.88 g of N-methylacetamide (NMA) (molar ratio 1:6) were mixed and stirred at 50 °C for 2 hours until completely dissolved to obtain LiTFSI / NMA electrolyte. 5 mL of the Fe3O4@TA@PVP nanoparticle dispersion (average particle size 138.4 nm) obtained in step (1) was placed on a neodymium iron boron magnet, and the Fe3O4@TA@PVP nanoparticles were collected by magnetic field. The supernatant was removed. The above LiTFSI / NMA electrolyte was added to the Fe3O4@TA@PVP nanoparticles and ultrasonically dispersed to obtain a magnetically responsive liquid electrolyte.
[0079] (4) Device fabrication: The AZO nanoparticle dispersion (spraying amount 1.5 mL) prepared in step (2) was sprayed onto a 3 cm × 3 cm BaF2 glass substrate and dried at 80 °C for 0.5 hours. Under an argon atmosphere, the temperature was increased to 280 °C at 5 °C / min and annealed at 280 °C for 30 minutes to form an AZO layer with a thickness of 1.0 μm on the BaF2 glass substrate, which is referred to as a BaF2 / AZO thin film. A 250 nm thick ITO transparent conductive layer was deposited on the surface of the AZO layer by magnetron sputtering to form a BaF2 / AZO / ITO stacked half-device. 3M adhesive was coated on the edge of the BaF2 / AZO / ITO stacked half-device, and ITO glass was used as the counter electrode for bonding and fixing to form a certain device cavity (thickness 0.8 mm). The prepared magnetically responsive liquid electrolyte was injected into the device cavity through a syringe to complete the device encapsulation. Figure 3 As shown, the device includes a BaF2 glass substrate, an AZO layer, an ITO transparent conductive layer, a magnetically responsive liquid electrolyte layer, and an ITO glass layer stacked sequentially.
[0080] Example 2 This embodiment provides a method for preparing a visible-mid-infrared biomimetic camouflage device based on multi-field synergistic regulation. The only difference from Embodiment 1 is that in step (1), the reaction temperature of TA and PVP in ethylene glycol is 130℃ (that is, in this Embodiment 2, 0.36 g of TA is added to 90 mL of ethylene glycol, stirred at room temperature for 5 minutes, then transferred to an oil bath preheated to 130℃, and after the temperature stabilizes, 15.0 g of PVP is slowly added and stirred at 130℃ for 20 minutes to obtain a uniform transparent solution).
[0081] Example 3 This embodiment provides a method for preparing a visible-mid-infrared biomimetic camouflage device based on multi-field synergistic regulation. The only difference from Embodiment 1 is that in step (1), the reaction temperature of TA and PVP in ethylene glycol is 160℃ (that is, in this Embodiment 3, 0.36 g of TA is added to 90 mL of ethylene glycol, stirred at room temperature for 5 minutes, then transferred to an oil bath preheated to 160℃, and after the temperature stabilizes, 15.0 g of PVP is slowly added, and stirred at 160℃ for 20 minutes to obtain a uniform transparent solution).
[0082] The materials and devices prepared in Examples 1, 2, and 3 were tested, and the results are as follows: (1) Scanning electron microscope images and particle size distribution statistics of Fe3O4@TA@PVP nanoparticles prepared at different temperatures in Examples 1, 2 and 3 are shown in the figure. Figure 4 As shown, the average particle sizes of Fe3O4@TA@PVP nanoparticles are 138.4 nm (prepared at 135℃), 162.7 nm (prepared at 130℃), and 109.5 nm (prepared at 160℃), and the particle surface exhibits a rough structure.
[0083] (2) Transmission electron microscopy (TEM) image and elemental distribution diagram of the Fe3O4@TA@PVP nanoparticles prepared in Example 1 (prepared at 135℃) are shown below. Figure 5 As shown, it is composed of smaller primary nanocrystal clusters.
[0084] (3) The hysteresis loop diagrams of Fe3O4@TA@PVP nanoparticles prepared at different temperatures (135℃, 130℃ and 160℃, respectively) in Examples 1, 2 and 3 are shown below. Figure 6 As shown, Fe3O4@TA@PVP nanoparticles exhibit typical superparamagnetic properties at room temperature, with a saturation magnetization of approximately 35 emu·g. -1 Coercivity and remanence are negligible.
[0085] (4) Transmission electron microscopy (TEM) image and LSPR curve of the AZO nanoparticles prepared in Example 1 are shown below. Figure 7 As shown, AZO nanoparticles are uniform in size, mainly distributed between 10 and 20 nm, and their local surface plasmon resonance (LSPR) absorption peaks are broadened, covering the mid- and far-infrared bands.
[0086] (5) The color changes and reflectance spectra of the visible-mid-infrared biomimetic camouflage devices prepared in Examples 1, 2 and 3 under different magnetic field intensities are shown in the figure. Figure 8As shown, for the device prepared in Example 1, as the magnetic field strength increases from 180 Gs to 1040 Gs, its apparent color changes from red-orange to blue-green, and the reflection peak wavelength shifts from 590 nm to 425 nm. For nanoparticles of different sizes, the magnetic field-dependent reflection peak shift range can reach 80~165 nm, covering a variety of structural colors such as red, orange, yellow, green, blue, and purple.
[0087] (6) The mid-infrared emissivity curves of the visible-mid-infrared bionic camouflage device in Example 1 under different voltages are shown in the figure below. Figure 9 As shown, the device achieves modulation rates of 0.314 and 0.249 in the 3–5 μm and 8–14 μm bands, respectively. It is noteworthy that this emissivity modulation behavior is not a binary switch, but rather allows for continuous and precise adjustment of the intermediate state by applying different bias voltages.
[0088] (7) For example Figure 10 As shown, the visible-mid-infrared biomimetic camouflage device prepared in Example 1 was placed on the surface of a heating stage at a constant temperature, and a bias voltage of ±3 V was applied to it alternately, switching every 15 s. By recording the surface temperature change curve over time in real time, it can be deduced that the response time of emissivity modulation is less than 2 s, and the apparent temperature fluctuation caused by the change in emissivity during this process is about 8.9℃.
[0089] (8) such as Figure 11 As shown, the visible-mid-infrared biomimetic camouflage device prepared in Example 1 exhibits highly consistent emissivity curves when a +3 V voltage is applied and the magnetic field strength is gradually increased (0~1000 Gs). Furthermore, no apparent temperature fluctuations caused by changes in the magnetic field are observed in the infrared thermal imaging results. These results demonstrate that controlling the visible light color through a magnetic field does not significantly affect the emissivity in the mid-infrared band (i.e., visible light modulation has no effect on mid-infrared emissivity).
[0090] (9) For example Figure 12 As shown, the visible-mid-infrared biomimetic camouflage device prepared in Example 1 was placed under a fixed magnetic field strength (240 Gs). Different voltages (±1 V, ±2 V and ±3 V) were applied to the device. The reflectance spectra of the device in the visible light band basically overlapped. At the same time, the visual observation results also showed that the color of the device did not change noticeably (i.e., the voltage modulation emissivity had no effect on the visible light response).
[0091] Therefore, the modulation of visible light and mid-infrared emissivity is achieved independently through magnetic and electric fields, respectively, and the two do not exhibit significant mutual coupling across the cross-band spectral range. Figure 13 Place the device against backgrounds of different colors, such as purple, green, and red. For example... Figure 14As shown, the structural color of the device is adjusted by an external magnetic field to achieve a high degree of visual integration with the background color.
[0092] In summary, this invention constructs a biomimetic camouflage device that can be independently, dynamically, and programmably controlled in the visible and mid-infrared bands through a biomimetic "functional decoupling and multi-field synergy" strategy, effectively solving the core bottleneck of strong coupling and lack of independence in multi-band spectral control in the prior art.
[0093] Example 4 This embodiment provides a method for fabricating a visible-mid-infrared biomimetic camouflage device based on multi-field synergistic modulation, including the following steps: (1) Synthesis of Fe3O4@TA@PVP nanoparticles: 0.36 g of TA was added to 90 mL of ethylene glycol and stirred at room temperature for 5 minutes. The mixture was then transferred to an oil bath preheated to 135 °C. After the temperature stabilized, 15.0 g of PVP was slowly added and stirred at 135 °C for 20 minutes to obtain a uniform and transparent solution. After the system cooled naturally to 65 °C, 1.62 g of ferric chloride hexahydrate (FeCl3·6H2O) was added and stirred at 65 °C for 40 minutes to obtain a dark green solution. The dark green solution was removed and slowly cooled to room temperature. Then, 8.4 g of sodium acetate (NaAc) was slowly added and stirred vigorously for 30 minutes. The resulting mixture was transferred to a polytetrafluoroethylene-lined reactor and reacted at 200 °C for 12 hours. After the reaction, the product was separated using a neodymium iron boron magnet and washed three times with ethanol. Finally, the product was dispersed in 80 mL of ethanol for later use to obtain a Fe3O4@TA@PVP nanoparticle dispersion.
[0094] (2) Synthesis of AZO nanoparticles based on continuous growth method: 1.0432 g (4.75 mmol) zinc acetate dihydrate, 0.0156 g (0.048 mmol) aluminum acetylacetonate, and 4.8 mL oleic acid were mixed and magnetically stirred at 110 °C under vacuum for 20 minutes. Then, 4.8 mL oleylamine was injected into the system, and stirring was continued at 100 °C under vacuum for 5 minutes to obtain a pretreated precursor solution. The system was then switched to a nitrogen atmosphere and maintained at this temperature for later use. 16 mL of oleyl alcohol was taken and vacuumed at 120 °C to remove water and oxygen. Then, the temperature was raised to 280 °C under nitrogen protection. 2.4 mL of the pretreated precursor solution was slowly injected into oleyl alcohol at 280 °C and reacted for 1 hour. After the reaction was completed, the mixture was cooled, purified by centrifugation, and dispersed in 15 mL of n-hexane to obtain an AZO nanoparticle dispersion.
[0095] (3) Preparation of pressure-responsive gel electrolyte: 2.87 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) was dissolved in 20 mL of propylene carbonate (PC) solvent and magnetically stirred until clear. 5.72 g of monomer 4-acryloylmorpholine, 0.198 g of crosslinking agent polyethylene glycol diacrylate, and 0.068 g of photoinitiator 1-hydroxycyclohexylphenyl ketone were added sequentially, and stirring was continued for 30 minutes to obtain a uniform photopolymerization electrolyte precursor solution. 5 mL of the Fe3O4@TA@PVP nanoparticle dispersion obtained in step (1) was placed on a NdFeB magnet, and Fe3O4@TA@PVP nanoparticles were collected by magnetic field. The above photopolymerization electrolyte precursor solution was added to the Fe3O4@TA@PVP nanoparticles and ultrasonically dispersed uniformly. The mixture was placed on the surface of the NdFeB magnet, and the direction and intensity of the magnetic field were adjusted until a bright structural color was observed. Subsequently, it was irradiated and cured under 365 nm wavelength ultraviolet light for 5 minutes to obtain the pressure-responsive gel electrolyte.
[0096] like Figure 15 As shown, the gel electrolyte exhibits a color change due to the altered spacing between its internal nanoparticles under mechanical pressure. Its ionic conductivity is measured to be 0.595 mS / cm, and its electrochemical stability window reaches ±3 V.
[0097] (4) The AZO nanoparticle dispersion (spraying amount 1.5 mL) prepared in step (2) was sprayed onto a 3 cm × 3 cm BaF2 glass substrate and dried at 80 °C for 0.5 hours. Under an argon atmosphere, the substrate was annealed at 280 °C for 30 minutes at a rate of 5 °C / min to form an AZO layer (thickness same as in Example 1) on the BaF2 glass substrate, which was referred to as a BaF2 / AZO thin film. An ITO transparent conductive layer (thickness same as in Example 1) was deposited on the surface of the AZO layer by magnetron sputtering to form a BaF2 / AZO / ITO stacked half-device. 3M adhesive was coated on the edge of the BaF2 / AZO / ITO substrate, and the pressure-responsive gel electrolyte (thickness same as the magnetically responsive liquid electrolyte layer in Example 1) was sandwiched between the BaF2 / AZO / ITO and the ITO glass to complete the device encapsulation.
[0098] In summary, this invention provides a visible-mid-infrared biomimetic camouflage device based on multi-field synergistic modulation, its fabrication method, and its applications. This invention achieves independent modulation of the visible and mid-infrared bands through a biomimetic "functional decoupling and multi-field synergy" strategy. Specifically, the visible light color can be independently changed (modulated visible light) by adjusting the lattice spacing of superparamagnetic nanoparticles in the electrolyte layer using a magnetic field or pressure. The absorption and reflection of infrared light by the material in the electroemissivity modulation layer can be changed by adjusting the ion / electron / carrier concentration using voltage, thereby independently changing the mid-infrared emissivity (modulated emissivity). These two methods do not interfere with each other, solving the core problem of strong band modulation coupling in traditional technologies. Simultaneously, the device provided by this invention can respond to various external stimuli such as magnetic fields, pressure, and electric fields, exhibiting strong environmental adaptability. The device provided by this invention achieves continuous tunability across the entire color gamut in the visible light band, with emissivity modulation rates of 0.314 and 0.249 in the mid-infrared 3–5 μm and 8–14 μm atmospheric windows, respectively. The apparent temperature change is 8.9 °C, and the response time is less than 2 seconds, meeting the requirements for dynamic camouflage. Furthermore, programmable patterned displays of the device can be achieved by controlling the spatial distribution of the magnetic field, providing a flexible and efficient solution for adaptive camouflage in complex backgrounds. It should be understood that the application of this invention is not limited to the examples described above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.
Claims
1. A visible-mid-infrared biomimetic camouflage device, characterized in that, The visible-mid-infrared biomimetic camouflage device comprises a transparent window layer, an electroemissivity modulation layer, an electrolyte layer, and a counter electrode layer stacked sequentially. The electrolyte layer includes an electrolyte matrix and superparamagnetic nanoparticles dispersed in the electrolyte matrix; The electroemission modulation layer includes at least one of aluminum-doped zinc oxide nanoparticles, carbon nanotubes, graphene, tungsten oxide, lithium titanate, and nickel oxide.
2. The visible-mid-infrared biomimetic camouflage device according to claim 1, characterized in that, The visible-mid-infrared biomimetic camouflage device further includes a transparent conductive layer located between the electroemissivity modulation layer and the electrolyte layer.
3. The visible-mid-infrared biomimetic camouflage device according to claim 1 or 2, characterized in that, The transparent window layer comprises one of BaF2, ZnS, ZnSe, polycarbonate, and polymethyl methacrylate; And / or, The superparamagnetic nanoparticles are superparamagnetic Fe3O4 nanoparticles, and polyvinylpyrrolidone is bonded to the surface of the superparamagnetic Fe3O4 nanoparticles.
4. The visible-mid-infrared biomimetic camouflage device according to claim 3, characterized in that, The surface of the superparamagnetic Fe3O4 nanoparticles is bonded with polyvinylpyrrolidone via tannic acid.
5. The visible-mid-infrared biomimetic camouflage device according to claim 4, characterized in that, The superparamagnetic Fe3O4 nanoparticles with polyvinylpyrrolidone bonded to their surface by tannic acid have a particle size of 50~300 nm.
6. The visible-mid-infrared biomimetic camouflage device according to claim 1 or 2, characterized in that, The electrolyte matrix includes a liquid electrolyte matrix or a gel electrolyte matrix; The liquid electrolyte matrix comprises a first lithium salt and a first organic solvent; The gel electrolyte matrix is formed by curing a second lithium salt, polymer monomer, crosslinking agent and photoinitiator.
7. A method for preparing a visible-mid-infrared biomimetic camouflage device according to any one of claims 1-6, characterized in that, Includes the following steps: Provide a transparent window layer; An electroemissivity modulation layer, an electrolyte layer, and a counter electrode layer are sequentially formed on the surface of the transparent window layer to obtain the visible-mid-infrared biomimetic camouflage device.
8. The preparation method according to claim 7, characterized in that, An aluminum-doped zinc oxide nanoparticle dispersion was applied to the surface of the transparent window layer, and after annealing, an electroemissivity modulation layer was formed. The preparation method of the aluminum-doped zinc oxide nanoparticle dispersion includes the following steps: Zinc acetate dihydrate, aluminum acetylacetonate, and oleic acid were mixed, heated and stirred under vacuum, and then oleylamine was injected and the mixture was heated and stirred again. The resulting mixture was then injected into oleyl alcohol preheated to 220-300°C for reaction. After centrifugation and purification, aluminum-doped zinc oxide nanoparticles were obtained. The aluminum-doped zinc oxide nanoparticles were dispersed in a second organic solvent to obtain an aluminum-doped zinc oxide nanoparticle dispersion.
9. The preparation method according to claim 7, characterized in that, The electrolyte layer contains superparamagnetic Fe3O4 nanoparticles with polyvinylpyrrolidone bonded to their surface via tannic acid. The preparation method of the superparamagnetic Fe3O4 nanoparticles with polyvinylpyrrolidone bonded to their surface via tannic acid includes the following steps: Tannic acid and polyvinylpyrrolidone were added to a third organic solvent and reacted at a temperature of 130-180°C. The mixture was then cooled to a preset temperature, ferric chloride hexahydrate was added, and stirring was continued. After cooling to room temperature, sodium acetate was added, and the mixture was stirred and reacted at a temperature of 180-220°C for 4-20 hours to obtain superparamagnetic Fe3O4 nanoparticles with polyvinylpyrrolidone bonded to their surface by tannic acid.
10. The application of a visible-mid-infrared bionic camouflage device according to any one of claims 1-6 in the fields of military camouflage, intelligent thermal control, or dynamic display.